2022
DOI: 10.1155/2022/2082445
|View full text |Cite
|
Sign up to set email alerts
|

New-Onset Lichen Planus Induced by the Pfizer COVID-19 Vaccine

Abstract: Objective Coronavirus disease 2019 (COVID-19) vaccine distribution continues to expand; however, increased cutaneous reactions have been reported. Several recent studies suggest a link between COVID-19 vaccination and the development of various cutaneous complications. Lichen planus is a chronic, immune-mediated, inflammatory dermatological illness with an unclear etiology. In this case report, we assessed the relationship between COVID-19 vaccination (Pfizer) and lichen planus diagnosis and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…Lack of confidence and knowledge is the main reason for vaccine hesitancy and non-vaccination. Numerous studies on vaccine safety that prompt hesitation about side effects [ 9 , 10 , 11 , 12 ] encourage the answers “I am afraid of the side effects” and “I do not trust the content of the vaccine”, which are among the reasons for not being vaccinated we found. The anti-vaccine “low disease threat” and “ineffectiveness of vaccines” arguments claimed by Dubé et al [ 30 ] are similar to the answers “not being thought to be protective” and “belief that the immune system will overcome the disease” in our study.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Lack of confidence and knowledge is the main reason for vaccine hesitancy and non-vaccination. Numerous studies on vaccine safety that prompt hesitation about side effects [ 9 , 10 , 11 , 12 ] encourage the answers “I am afraid of the side effects” and “I do not trust the content of the vaccine”, which are among the reasons for not being vaccinated we found. The anti-vaccine “low disease threat” and “ineffectiveness of vaccines” arguments claimed by Dubé et al [ 30 ] are similar to the answers “not being thought to be protective” and “belief that the immune system will overcome the disease” in our study.…”
Section: Discussionmentioning
confidence: 86%
“…Many new studies on this subject have increased these questions. For example, some research findings have suggested a link between the COVID-19 vaccination and the development of various cutaneous complications [ 9 , 10 , 11 ]. However, another study claiming no “zero risk” vaccinations exist uncovered rare cases of thrombosis in patients vaccinated with mRNA COVID-19 vaccines [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] Numerous clinical studies have shown that the majority of vaccines cause a Th1 response, increasing the serum levels of interleukin (IL)-2, tumour necrosing factor (TNF) and interferon (IFN), which are involved in the onset of lichen planus. [ 8 ] Up-regulation of Th1 and an increase in pro-apoptotic cytokines like TNF and IFN have been identified as important factors responsible for the basal keratinocyte death found in this skin disorder, despite the fact despite the fact that the exact pathophysiology is unknown. These vaccines may consequently induce an increase in some skin conditions brought on by the aforementioned factors.…”
Section: Discussionmentioning
confidence: 99%
“…Po drugiej dawce tej samej szczepionki wykwity w postaci przerostowych, wielobocznych grudek i blaszek rozprzestrzeniły się na klatkę piersiową i ramiona. Autorzy podali, że zmiany ustąpiły po 3-tygodniowym stosowaniu glikokortykosteroidów miejscowo [37].…”
Section: Discussionunclassified
“…After the second dose of the same vaccine, hypertrophic, polygonal papules and plaques spread to her chest and shoulders. Alghamdi et al revealed that the lesions responded to treatment with topical glucocorticosteroids for 3 weeks [37].…”
Section: Articles That Reported the Onsetmentioning
confidence: 99%